Profit sharing and risk management via mudarabah in the modern practice of some financial institutions - mohamed Bulushi, Ibrahim; Mahmud, Mek Wok (IIUM Press, International Islamic University Malaysia, 2017)
The evolution and introduction of Islamic financial institutions in the last three decades have generated issues and arguments among Muslim economists, scholars and practitioners. What is in relation to the theories of profitsharing in the context of muÌÉrabah and its risk management in the modern Islamic financial institutions (MIFI) have remained the most discussed issue in the Islamic financial industries. The present study analyses profit sharing in the context of muÌÉrabah and its risk management in the modern Islamic Financial institutions (MIFI) by examining the application of muÌÉrabah and its constituents from the classical perspective to the contemporary issues. The study scrutinizes and answers the research hypotheses by using surveyed data from Islamic financial institutions in Malaysia. The construct validity of Modern Islamic financial Institutions (MIFI) reveals that profit sharing (PS) in the institutional context is explored by several approaches; muÌÉrabah application from classical to contemporary issues. It evaluates the basis of PS theory by considering the relevant literature on mudÉrabah and risk management in Islamic financial institutions by establishing fundamental issues which add to one of the challenges faced by modern Islamic financial institutions (MIFI).